THIRD COUNTRY IMPACT OF EU ANTI-DUMPING MEASURES - Cuyvers, Ludo; Zhou, Weifeng (Journal of European Economy, 2017)
This paper investigates the impact of EU antidumping measures on the targeted country and non-targeted country. A three-country model is employed to examine the trade destruction, trade diversion, trade deflection and trade depression effects associated with the EU antidumping measures imposed on China and the US during the 1995–2005 period. The findings suggest that EU antidumping measures against China destroy Chinese exports to the EU and lead to an increase of Chinese exports to the US (trade deflection). Further, EU antidumping measures on US exports divert Chinese exports in the same products to the EU and lead to a reduction of Chinese exports in the same products to the US (trade depression).